Depression of adenosylmethionine content of Escherichia coli by thioglycerol. - Javor, G T (1983)
The mechanism of growth inhibition of Escherichia coli by thioglycerol was probed. The extent of growth inhibition depended on the ratio of thioglycerol to initial cell concentration. Exogenously added methionine and several methionine analogues reversed the inhibition of 2 to 40 mM thioglycerol. Exposure to thioglycerol elevated the intracellular concentration of methionine, but the level of S-adenosylmethionine was depressed. Thioglycerol was methylated in vivo to 3-methylthio-1,2-propanediol.